Monitoring land use changes and soil degradation using spot and temporal aerial photograph data - the case of Vathy basin (Kalymnos island - Dodecanese Greece) - Mimides, T.; Psomiadis, E.; Trikili, I. (Bulletin of the Geological Society of Greece, 2007)
The present paper focuses on the usefulness of aerial photographs and satellite data in the multitemporal detection of land use changes, soil degradation and erosion. The study was carried out in the watershed of Vathy in the Kalymnos Island, and the study period spanned from 1960 to 1999. Aerial photographs of two different periods of time and satellite SPOT data were used for this purpose. The synergistic use of a Geographical Information System for the manipulation of the data was the key for the Natural monitoring of the soil erosion and degradation. The results revealed many changes in the cultivations and in the land use of the watershed the last decades. These changes supplemented by village expansion and spatial reduction of natural vegetation led to the acceleration of soil erosion, to the degradation of water supplies and generally to an environmental deterioration of the wider area.